Dimensions of stress in parents of children with autistic spectrum disorder - Bakri, Amirah Hazwani Binti; Rosli, Noor Aishah Binti; Mohd Kasirun, Zarinah Binti; Md Nasir, Mohd Hairul Nizam Bin; Othman, Fazidah Binti; Tengku Kasim, Tengku Sarina Aini Binti (Makara Journal of Health Research, 2019)
Background: Parents of children with Autistic Spectrum Disorder (ASD) are at an increased risk for stress and other mental health problems. While treatment is mainly focused on the child, somehow parents’ stress is exacerbated. Accordingly, the purpose of this study was to identify the sources of stress in the parents of children with ASD. Methods: The 52 parents of children with ASD who participated in the study completed the child domain (CD) and parent domain (PD) subscales of the Parenting Stress Index Fourth Edition (PSI-4). Subsequently, the scores of the PSI-4 subscales were analyzed and compared. Results: The respondents scored the highest for the distractibility/hyperactivity subscale in the child domain and highest for the depression subscale in the parent domain. Conclusion: The results of this study may help to determine suitable treatment for parents of children with ASD. Child and parent characteristics contribute equally to parental stress, distractibility/hyperactivity and depression were most prevalent in the CD and PD respectively.